(untitled) (Research, Society and Development, 2022)
This article presents a protocol for a scoping literature review. The scoping review is characterized as a type of review systematically conducted that aims to carry out a mapping of concepts, theories, sources of evidence in a given area of research, enabling in-depth exploration of the literature, mapping and summarizing contente and identifying gaps and directions for further research. Conducted in accordance with the Joanna Briggs Institute (JBI) scoping review production guide, together with the guidelines of the Prefered Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (Prisma-ScR), the study of the presente protocol is governed by the following guiding question: “ what does the literature report about the role of Occupational Therapy in promoting health with adolescentes?, prepared based on the PCC Mnemonic (Population - studies that address the role of Occupational Therapy with adolescents; Concept - texts in which the authors characterize intervention processes in Occupational Therapy explicitly as health promotion and/or well-being actions Context – identified from the contexts in which occupational therapy actions aimed at promoting health in adolescence take place). Searches will be carried out in PubMed, LILACS, CINAHAL, PsycoInfo, Web of Science, Scopus and Scielo databases, together with manual searches in specific Occupational Therapy journals. The research results and the reflections arising from it will be systematized in a report in the form of a scientific article, which will be sent for analysis and possible publication in a scientific journal.